Value of ocular trauma score in predicting the incidence of secondary glaucoma after closed globe injury. Issue 5 (September 2022) - Hou, Xu; Guo, Xinxing; Cui, Zhili; Wang, Yusheng; Zhou, Jian; Hu, Dan
Aim: To analyze the visual acuity (VA) and the incidence of secondary glaucoma among patients with closed globe injury (CGI). To determine the correlations between the ocular trauma score (OTS) with surgery rate, and evaluate the applicability of OTS in secondary glaucoma prediction and treatment. Methods: We conducted a retrospective review of 265 patients (265 eyes) with CGI admitted to Xijing Hospital between January 2014 and December 2016. The clinical characteristics; VA, IOP, injury zone, surgery, and IOP-lowering medications were collected at the initial visit and at six months. The patients with secondary glaucoma were scored and assessed by the OTS system. The correlation of the anti-glaucoma surgery with the OTS was evaluated. The difference in the number of IOP-lowering medications between the initial visit and six months was analyzed. Results: The average age of the patients was 33.5 ± 20.7 years with 80.8% being males. The final VA outcome improved in its totality after treatment. 35 patients developed glaucoma, with an incident rate of 13.2% over six months. All glaucoma patients had an injury in zone I and II, and 12 of them had an injury in zone III. The severity of the OTS category showed a strong correlation with the anti-glaucoma surgery rate. After the surgical intervention, the number of IOP-lowering medications in OTS category 2, 3, and 4 significantly reduced. Conclusions: The OTS has predictive value in the incidence of secondary glaucoma after CGI. A patient with a low score is more likely to develop secondary glaucoma and might require surgical intervention.